Pawnshops in the Perspective of Islamic Law - Ilyas, Rahmat (al-'adalah, 2019)
The development of the economy and the business world will always be followed by the development of the need for credit and the provision of credit facilities that always require collateral. This is for the security of the provision of credit in the sense that the loan received will be guaranteed by guarantee. In this context the importance of the guarantee institution lies. Pawn is a guarantee institution that has been very well known in people's lives in their efforts to get funds for various needs. Pawnshops is a state-owned enterprise in Indonesia whose core business is in the field of lending/loan services to the public on the basis of mortgage law. In Indonesia the legal basis of Pawnshop are: the MUI DSN fatwa No. 25 / DSN-MUI / III / 2002 dated June 26, 2002 concerning rahn which states that loans with mortgaged goods as collateral for debt in the form of rahn are permitted; the MUI DSN fatwa No.26 / DSN-MUI / III / 2002 concerning gold pawning; as well as the MUI DSN fatwa No. 68 / DSN-MUI / III / 2008 about rahn Tasjily